FRENCH “FIDUCIE” AND RUSSIAN “ДОВЕРИТЕЛЬНОЕ УПРАВЛЕНИЕ ИМУЩЕСТВОМ” (TERMINOLOGICAL PECULIARITIES) - Irina Gvelesiani (European Scientific Journal, ESJ, 2014)
“Trust” is “the greatest and most distinctive achievement performed by Englishmen in the field of jurisprudence”. This universal institution appeared in the Medieval English law and has become very popular during the last decades. Different variations of a trust mechanism have emerged in some world countries. The given paper tries to answer the demands of the modern epoch via making a precise description of the French and Russian trust-like devices. It makes an in-depth analysis, singles out major terminological units and underlines the fact, that the newly-established French and Russian mechanisms have to undergo several stages for turning into faithful reflections of the Anglo-American model of “trust”.